An ALPK3 truncation variant causing autosomal dominant hypertrophic cardiomyopathy is partially rescued by mavacamten - Lisa Leinhos; Paul Robinson; Giulia Poloni; Sophie Broadway-Stringer; Julia Beglov; Adam B. Lokman; Gillian Douglas; Sajjad Nuthay; Oveena Fonseka; Manuel Schmid; Evie Singer; Charlotte Hooper; et al. (Scientific Reports)
Abstract The ALPK3 gene encodes alpha-protein kinase 3, a cardiac pseudo-kinase of unknown function. Heterozygous truncating variants (ALPK3tv) can cause dominant adult-onset hypertrophic cardiomyopathy (HCM). Here we confirm an excess of ALPK3tv in sarcomere-gene negative HCM patients. Moreover, we generated a novel knock-in mouse model carrying an ALPK3tv (K201X). Homozygous animals displayed hypertrophy and systolic dysfunction. Heterozygous animals demonstrated no obvious baseline; however, they had an aggravated hypertrophic response upon chronic adrenergic challenge. Isolated, unloaded cardiomyocytes from heterozygous and homozygous mice showed reduced basal sarcomere length with prolonged relaxation, whilst calcium transients showed increased diastolic calcium levels. Protein kinase A-mediated phosphorylation, including that of cardiac troponin I, was significantly decreased. In agreement with the cellular HCM phenotype, reduced ratios of myosin heads in the super-relaxed state were measured. Contractile and calcium handling defects were partly corrected by treatment with mavacamten, a novel myosin inhibitor. For the first time with a non-sarcomere HCM variant, we have demonstrated hallmark changes in cardiac contractility and calcium handling. Mavacamten is able to partially rescue the cellular phenotype, hence could be beneficial to HCM patients with ALPK3tv. Moreover, our data points at a potential role of ALPK3 as a modulator of protein kinase A signalling.